Development of a photoelectrode based on a bismuth(iii) oxyiodide/intercalated iodide-poly(1H-pyrrole) rough spherical nanocomposite for green hydrogen generation - Alkallas Fatemah H.; Trabelsi Amira Ben Gouider; Elsayed Asmaa M.; Rabia Mohamed (Open Physics, 2025)
This study presents the innovative design and development of a bismuth(iii) oxyiodide/intercalated iodide-poly(1H-pyrrole) rough spherical nanocomposite (Bi(iii)OI/I-P1HP RS-nanocomposite) as a next-generation photocathode for sustainable hydrogen production directly from seawater. The material features a unique rough-surfaced spherical morphology, composed of finely distributed nanoparticles averaging 15 nm in diameter, which enhances the surface area and light interaction. The strategic incorporation of iodide components significantly boosts photon absorption, while the optimal bandgap of 2.45 eV enables efficient light harvesting from the ultraviolet to mid-visible spectral range – ideal for real-world solar-driven applications. Hydrogen evolution experiments conducted using both natural Red Sea seawater and a synthetically formulated laboratory electrolyte demonstrated consistent and efficient performance, with current densities (J ph) in light of −0.20 and −0.19 mA cm⁻2, respectively. These values correspond to an impressive hydrogen production rate of 5.0 µmol h−1 cm−2. The photocathode exhibited remarkable operational stability and reproducibility under chopped illumination, confirming its robustness under dynamic light conditions. Furthermore, spectral response studies across various wavelengths revealed adaptable behavior based on photon energy, underscoring its versatility in different lighting environments. With its compelling combination of high photoelectrochemical efficiency, structural stability, and economic viability, the Bi(iii)OI/I-P1HP RS-nanocomposite emerges as a promising candidate for scalable, eco-friendly hydrogen generation. This work lays the foundation for future industrial applications in renewable energy, offering a practical and sustainable route toward clean fuel production directly from seawater.